A new canid species (Carnivora: Canidae) from the Plio-Pleistocene hominin-bearing site of Kromdraai (Cradle of Humankind, Gauteng, SouthAfrica) - (:unkn) unknown (My University, 2022)
The Plio-Pleistocene site of Kromdraai, coveringa chronological range from 1.8 Ma (Kromdraai A Locality) up to older than 2.0 Ma (Kromdraai Member 2), (Cradle of Humankind, Gauteng, South Africa) has been investigatingsince the first half of the XXth century. These researches have led to the discovery of the type specimen of Paranthropus robustus. Kromdraai is also characterized by an extremely rich bone accumulation (includingmore than 8200 remains with more than 2200 from the recent field works). Carnivores are highly diverse including Felidae, Hyaenidae, Herpestidae, Viverridae, Mustelidae and Canidae. Based on 27 newly discovered dental and postcranial specimens, a new canid species is described. Canis hewitti sp. nov. is comparable in size to the extant African huntingdogLycaon pictus but it differs significantly from this species in dental features that are typical of the genus Canis incuding the m1 with a trigonid of about two-thirds the length of the crown, a metaconid clearly dissociated from the protoconid and a talonid consistingin a hypoconid and an entoconid. Its premolars suggest a certain specialization in meat-cutting(longand thin p4 with a high protoconid backwardly flanked of a well-developed cusp followed by an accessory small denticle). C. hewitti appears as the potential ancestor of the more robust southern African Canis atrox from Kromdraai A (ca. 1.8 Ma).
Keywords: African Research